THE ROLE OF REGIONAL INVESTMENT FLOWS IN UZBEKISTAN AND ITS ATTRACTIVE FACTORS - Samadhi , Dilli; Deepan, Deepan; Shayzakokva, Shaxnoza (Scientific practical conference, 2026)
This article analyzes the processes of forming investment flows in the regions of Uzbekistan based on statistical data. Factors determining the investment attractiveness of regions will be identified, and scientifically grounded proposals for their improvement will be developed.